Effect of pediatric massage technique on intestinal function recovery of after surgery for congenital intestinal atresia in children (小儿推拿技术对先天性肠闭锁患儿术后肠功能恢复的影响研究) - LI Huixian (李会仙); YUAN Jie (袁洁); ZHANG Xiaohui (张晓辉); LIANG Shuo (梁硕) (中西医结合护理)
Objective To investigate the effect of pediatric massage technique on intestinal function recovery after surgery for congenital intestinal atresia in children. Methods A total of 60 children with congenital intestinal atresia admitted to the hospital from January 2021 to October 2024 were selected as the study objects. They were randomly divided into control group (30 cases) and observation group (30 cases). The control group was given routine care, including maintaining stable body temperature, maintaining good respiratory function, continuous gastrointestinal decompression, intravenous parenteral nutrition solution, preventing incision infection, etc. On the basis of routine nursing, the observation group began to implement pediatric massage technology on the second day after surgery until total intestinal feeding was achieved. The postoperative bowel sound recovery time, first defecation time, time of postoperative feeding and time to full enteral feeding were compared between the two groups. Results The recovery time of bowel sound, the time of first defecation, time of postoperative feeding and time to full enteral feeding in the observation group were shorter than those in the control group, with significance difference (P<0. 01). Conclusion The application of pediatric massage technology on the basis of routine nursing for children with congenital intestinal atresia has significant effect on the recovery of intestinal function, which can shorten the time to full enteral feeding and improve the prognosis of children. (目的 探讨小儿推拿技术对先天性肠闭锁患儿术后肠功能恢复的影响。方法 选取医院2021年1月—2024年10月收治的60例先天性肠闭锁患儿为研究对象, 随机分为对照组(n=30)和观察组(n=30)。对照组患儿术后给予维持体温稳定、保持良好的呼吸功能、持续胃肠减压、静脉输注肠外营养液、预防切口感染等常规护理; 观察组在常规护理的基础上, 术后第二天开始实施小儿推拿技术, 直到达到全肠道喂养为止。比较两组患儿术后肠鸣音恢复时间、首次排便时间、达到全胃肠道喂养时间等。结果 观察组术后肠鸣音恢复时间、肛门首次排便时间早于对照组, 差异有统计学意义(P＜0. 01); 观察组术后开始喂养时间及达到全肠道喂养时间少于对照组, 差异有统计学意义(P＜0. 01)。结论 对先天性肠闭锁患儿术后实施常规护理的基础上, 应用小儿推拿技术对肠功能恢复效果明确, 可缩短全胃肠道喂养时间, 对患儿预后具有重要意义。)